Applicability of the 2013 ACC/AHA Risk Assessment and Cholesterol Treatment Guidelines in the real world: results from a multiethnic case-control study. (18th May 2016) - Magnoni, Marco; Berteotti, Martina; Norata, Giuseppe Danilo; Limite, Luca Rosario; Peretto, Giovanni; Cristell, Nicole; Maseri, Attilio; Cianflone, Domenico
Abstract: Background : The 2013 ACC/AHA cholesterol treatment guidelines have introduced a new cardiovascular risk assessment approach (PCE) and have revisited the threshold for prescribing statins. This study aims to compare the ex ante application of the ACC/AHA and the ATP-III guideline models by using a multiethnic case-control study.Methods : ATP-III-FRS and PCE were assessed in 739 patients with first STEMI and 739 age- and gender-matched controls; the proportion of cases and controls that would have been eligible for statin as primary prevention therapy and the discriminatory ability of both models were evaluated.Results : The application of the ACC/AHA compared to the ATP-III model, resulted in an increase in sensitivity [94% (95%CI: 91%–95%) vs. 65% (61%–68%), p< 0.0001], a reduction in specificity [19% (15%–22%) vs. 55% (51%–59%), p< 0.0001] with similar global accuracy [0.56 (0.53–0.59) vs.0.59 (0.57–0.63), p ns]. When stratifying for ethnicity, the accuracy of the ACC/AHA model was higher in Europeans than in Chinese (p = 0.003) and to identified premature STEMI patients within Europeans much better compared to the ATP-III model (p = 0.0289).Conclusion : The application of the ACC/AHA model resulted in a significant reduction of first STEMI patients who would have escaped from preventive treatment. Age and ethnicity affected the accuracy of the ACC/AHA model improving the identification of premature STEMI among Europeans only. Key messages: According to the ATP-III guideline model, about one-third of patients with STEMI would not be eligible for primary preventive treatment before STEMI. The application of the new ACC/AHA cholesterol treatment guideline model leads to a significant reduction of the percentage of patients with STEMI who would have been considered at lower risk before the STEMI. The global accuracy of the new ACC/AHA model is higher in the Europeans than in the Chinese and, moreover, among the Europeans, the application of the new ACC/AHA guideline model also improved identification of premature STEMI patients.